Sex-specific associations of cardiovascular risk factors and coronary plaque composition for hemodynamically significant coronary artery stenosis: a coronary computed tomography angiography study - Mengshan Wu; Jintang Feng; Zhang Zhang; Ningnannan Zhang; Fan Yang; Ruijun Li; Yueqi Men; Dong Li (BMC Cardiovascular Disorders, 2023)
Abstract Background It has been reported that there are sex differences in plaque composition and hemodynamically significant stenosis. This study aimed to explore the impact of sex on cardiovascular risk factors for specific plaque compositions and hemodynamically significant stenosis. Methods Data regarding demographics and cardiovascular risk factors were collected. Hemodynamically significant stenosis was identified by a computed tomography-derived fractional flow reserve of ≤ 0.8. Associations among cardiovascular risk factors, plaque composition, and hemodynamically significant stenosis were assessed using a multivariate binary logistic regression analysis across sexes. The discriminating capacity of diverse plaque components for hemodynamically significant stenosis was assessed by area under the receiver-operating characteristics curve with 95% confidence intervals. Results A total of 1164 patients (489 men and 675 women) were included. For men, hyperlipidemia and cigarette smoking were risk factors for each plaque component (all P < 0.05), and diabetes mellitus also predicted fibrotic components (P < 0.05). For women, risk factors for each plaque component were hypertension and diabetes mellitus (all P < 0.01). Nonetheless, hyperlipidemia (P < 0.05) was a specific risk factor for non-calcified components. Calcified components combined with fibrotic components showed superior discrimination of hemodynamically significant stenosis in men and calcified components alone in women (all P < 0.01). Hypertension (P < 0.01) was a risk factor for hemodynamically significant stenosis in women. In contrast, diabetes, hyperlipidemia, and cigarette smoking were risk factors for hemodynamically significant stenosis in men (all P < 0.05). Conclusions In men, hemodynamically significant stenosis was predicted by a combination of calcified and fibrotic components with multiple risk factors. In women, hemodynamically significant stenosis was predicted by calcified components caused by a single risk factor. It might be a key point to improve prognosis by more precise risk management between men and women, which needs to be proved by further prospective trials.